2018
DOI: 10.1007/s12105-018-0990-7
|View full text |Cite
|
Sign up to set email alerts
|

SOX10 Immunoexpression in Basaloid Squamous Cell Carcinomas: A Diagnostic Pitfall for Ruling out Salivary Differentiation

Abstract: SOX10 immunoexpression is increasingly recognized in salivary gland tumors, including but not limited to those with myoepithelial, serous acinar, and intercalated duct differentiation. However, SOX10 expression has not been extensively evaluated in other epithelial tumors that can mimic salivary origin. Basaloid squamous cell carcinoma (SCC) is a unique variant of SCC that shows morphologic overlap with several salivary tumors, including adenoid cystic carcinoma, basal cell adenocarcinoma, and myoepithelial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…1d). IHC can also facilitate this distinction, with only focal expression of myoepithelial markers such as S100 and SMA in basaloid SCC [20,21]; however, frequent reactivity for c-kit [22] and SOX10 [23] in basaloid SCC can pose a pitfall. FISH for MYB rearrangements can confirm a classification as ACC, but a negative result does not exclude this diagnosis [11,12].…”
Section: Challenge #1: Squamous Differentiationmentioning
confidence: 99%
“…1d). IHC can also facilitate this distinction, with only focal expression of myoepithelial markers such as S100 and SMA in basaloid SCC [20,21]; however, frequent reactivity for c-kit [22] and SOX10 [23] in basaloid SCC can pose a pitfall. FISH for MYB rearrangements can confirm a classification as ACC, but a negative result does not exclude this diagnosis [11,12].…”
Section: Challenge #1: Squamous Differentiationmentioning
confidence: 99%
“…The Sry-related HMG box10 gene (SOX10) encodes a transcription factor that plays a crucial role in the survival, maturation, and differentiation of neural crest-derived melanocytes and glia. 22,23 SOX10 was reported to be preferentially expressed in metaplastic breast carcinomas. 24 Because of fewer cases (only 4 cases of metaplastic carcinomas mixed squamous with spindled and chondroid components), the expression of SOX10 in MSCCB remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The positivity for p63 and negativity for neuroendocrine markers also distinguishes basaloid SCC from the rare entity of HPV-associated neuroendocrine carcinoma of the oropharynx, which has the opposite immunophenotype [ 53 , 54 ]. Interestingly, a recent study of basaloid SCC showed that a majority of tumors were positive for SOX10 [ 55 ], a feature shared with most cylindromas [ 56 , 57 ], as well as some many other cutaneous adnexal tumors and salivary gland tumors [ 58 ].…”
Section: Discussionmentioning
confidence: 99%